Second primary cancers in melanoma patients critically shorten survival - Zheng, Guoqiao; Chattopadhyay, Subhayan; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (Clinical epidemiology, 2020)
Second Primary Cancers in Melanoma Patients Critically Shorten Survival Guoqiao Zheng,1,2 Subhayan Chattopadhyay,1,2 Kristina Sundquist,3- 6 Jan Sundquist,3- 6 Asta Försti,1,3 Akseli Hemminki,7,8 Kari Hemminki1,3,9,9 1Division of Molecular Genetic Epidemiology, German Cancer Research Center (DKFZ), Heidelberg D-69120, Germany; 2Faculty of Medicine, University of Heidelberg, Heidelberg, Germany; 3Center for Primary Health Care Research, Lund University, Malmö 205 02, Sweden; 4Department of Family Medicine and Community Health, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 5Department of Population Health Science and Policy, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 6Center for Community-based Healthcare Research and Education (CoHRE), Department of Functional Pathology, School of Medicine, Shimane University, Matsue, Shimane, Japan; 7Cancer Gene Therapy Group, Translational Immunology Research Program, University of Helsinki, Helsinki, Finland; 8Comprehensive Cancer Center, Helsinki University Hospital, Helsinki, Finland; 9Faculty of Medicine and Biomedical Center in Pilsen, Charles University in Prague, Pilsen 30605, Czech RepublicCorrespondence: Guoqiao ZhengDivision of Molecular Genetic Epidemiology, German Cancer Research Center (DKFZ), Im Neuenheimer Feld 580, Heidelberg 69120, GermanyTel +49-6221-421805Fax +49-6221-421810Email g.zhengdkfz.deBackground: Survival in malignant cutaneous melanoma has improved but increasing survival will result in an increased likelihood of the occurrence of second primary cancers (SPCs). SPCs may adversely interfere with survival. We quantified survival in patients with different types of SPCs, in comparison to known poor prognostic indicators of metastatic disease.Methods: Data for melanoma and any SPCs were obtained from the Swedish Cancer Registry for years 2003 through 2015, including clinical TNM classification. SPCs were grouped into three ‘prognostic groups’ based on 5-year relative survival of these cancers as first primary cancer. Kaplan-Meier survival curves were generated and hazard ratios were estimated using Cox regression, adjusted for a number of variables and treating diagnosis of SPC as a time-dependent variable.Results: The total number of first melanoma patients was 28,716 followed by 3,202 (11.1%) SPCs, 1/3 of which had a second melanoma while 2/3 had other SPCs. Among men diagnosed at age over 70 years, who survived at least 10 years, 31.4% had SPC. HRs (95% CI) for survival increased systematically from the reference rate of 1.00 (no SPC) to 1.59 (1.35- 1.87) with SPC of good prognosis (78.6% of SPCs) to 3.49 (2.58- 4.72) of moderate prognosis (12.0%) and to 7.93 (5.50- 11.44) of poor prognosis (9.4%). In patients without SPC, the HRs increased to 2.62 (2.02- 3.39) with any nodal metastases and to 5.88 (4.57- 7.57) with any distant metastases compared to patients without local or distant metastases.Conclusion: The data showed that SPCs are an increasingly common negative prognostic factor for melanoma. Future attempts to improve melanoma survival need to target SPCs.Keywords: melanoma, second cancer, metastasis, prognosis, survival